Peningkatan Kreativitas Melalui Penggunaan Bubur Kertas sebagai Media Pratikum dalam Pembelajaran Seni Rupa pada Siswa Kelas VIII.1 SMPN 3 Batusangkar - Rafid Putra; Yusron Wikarya (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research was carried out in an effort to increase creativity through the use of paper pulp as a practical medium in fine arts learning for class VIII.1 students at SMPN 3 Batusangkar. This research is classroom action research, with the collection tools being observation and questionnaires. The research procedure is in the form of a cycle which includes four steps, namely planning, action, observation and reflection. The research instrument uses a creativity questionnaire and activity observation sheet. Data analysis was carried out via t test with the SPSS program. The research results showed that there was an increase in student creativity through the use of paper pulp as a practical medium in fine arts learning for Class VIII.1 students at SMPN 3 Batusangkar. In the pre-cycle, the percentage of student creativity was 65.60%. In cycle I, the percentage of student creativity was 72.70%. In cycle II, the percentage of student creativity was 88.81%.